PELATIHAN DAN PENYEDIAAN FASILITAS PRAKTEK CTPS-5W CEGAH COVID-19 - Christina Olly Lada; Ika Febrianti; Rr Listyawati Nurina; Almido H. Ginting (Universitas Nusa Cendana, 2021)
Personal hygiene of children is very important to support their health. One of the personal hygiene practices is handwashing with water and soap (HWWS) at five important which preschool and school children have not been able to practice properly. The five important times of HWWS are before eating, after eating, after going to the toilet (to defecate or urinate), after doing activities or touching objects, .transmitted when contaminated hands touch the nose, mouth, or eyes. As a result, the virus will invade the body and have an impact on airway disorders. To overcome this problem, training activities and practices on how to wash hands properly using soap were carried out. By being given knowledge about personal hygiene such as washing hands with soap five times (HWWS-T5), children will be able to wash their hands properly and correctly, which can prevent transmission of the coronavirus and other communicable diseases.